Poti k romanu - Zupan Sosič, Alojzija (Primerjalna književnost, 2001)
Paths to a novel. - Syncretism is the oldest invariable of the novel. In the last decade of the 20th century the only regular novelistic feature is most visible in the contemporary Slovene novel in the genre syncretism of novelistic structures, which combines different genres. - Genre hybridism, or the interrelatedness of various novelistic genres within one novel, has balanced different narrative procedures, and by tending to have a dominant genre foundation, 'built' a clear storyline. Since the novel of the 1990s is a modified traditional novel, genre syncretism represents the most important transformed tendency for it, while, at the same time, it directs metaliterary paths to the novel through a multi-layered genre analysis. In the novels of young authors (born after 1958) this has pointed towards renewed positions of traditional genres (anti-utopian, horror, historical, crime, travelogue, love and socio-critical novel) and interesting novelties of this period (novels andnovels of landscape fiction). - In addition to genre syncretism, there are two other important 'transformers' of traditional genre formulas, the non-typical position of the narrator and an increased number of spoken passages. The transformational role of the narrator with an ironical-satirical perspective introduces a new (most often post-modernist) relation between the story and the reader, while the dynamic dialogues make the modern Slovene novel more like a screenplay. - The balanced union of the traditional and contemporary novelistic features has not only promoted the flowering of the Slovene novel, but at the end of the century, and with increased reading appeal, it has also paved the way for a new reading.
Keywords: Slovene literature; slovenska književnost; slovenski roman; literarna teorija; literary theory